ChemInform Abstract: Copper‐Catalyzed Cascade Transformation of O‐Propargylic Oximes with Sulfonyl Azides to α, β‐Unsaturated N‐Acylamidines. Issue 12 (March 2015) - Zhang, Dong; Nakamura, Itaru; Terada, Masahiro
Abstract The title reaction involves the intramolecular attack of the oxime group to the in situ generated ketenimine moiety, followed by cleavage of the N—O bond.